2008
DOI: 10.1016/j.mad.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function, muscle strength and mortality in old age

Abstract: Numerous reports have linked extremity muscle strength with mortality but the mechanism underlying this association is not known. We used data from 960 older persons without dementia participating in the Rush Memory and Aging Project to test two sequential hypotheses: first, that extremity muscle strength is a surrogate for respiratory muscle strength, and second, that the association of respiratory muscle strength with mortality is mediated by pulmonary function. In a series of proportional hazards models, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
1
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 41 publications
2
94
1
7
Order By: Relevance
“…Our results support the hypothesis that muscle strength loss initiates the causal chain that contributes to decreased pulmonary function and mobility limitations (Buchman et al 2008). The mechanisms behind age-related changes in muscle tissue are most likely a combination of systemic physiological mechanisms (hormonal and neural changes, increased inflammation, reduced protein synthesis, increased muscle proteolysis, decreased regenerative capacity, motor neuron loss and reduced excitability, decreased central drive, and increased muscle/fat content etc.)…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results support the hypothesis that muscle strength loss initiates the causal chain that contributes to decreased pulmonary function and mobility limitations (Buchman et al 2008). The mechanisms behind age-related changes in muscle tissue are most likely a combination of systemic physiological mechanisms (hormonal and neural changes, increased inflammation, reduced protein synthesis, increased muscle proteolysis, decreased regenerative capacity, motor neuron loss and reduced excitability, decreased central drive, and increased muscle/fat content etc.)…”
Section: Discussionsupporting
confidence: 84%
“…It has been suggested that a decline in muscle strength initiates a chain of events which leads to reduced pulmonary function and low physical performance and mobility disability (Buchman et al 2008). Reduced chest wall compliance, kyphosis and decreased respiratory muscle strength and endurance are examples of age-related musculoskeletal changes that may have an effect on pulmonary functions (Meyer 2005;Stanojevic et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Then we examined the various combinations of these three factors together, first in combinations and then finally with all three in a single model ( Table 2, Models D-G). In these models, an attenuation of the association of muscle strength with mobility disability when pulmonary function was added into the model would support the hypothesis that muscle strength and mobility disability are linked (mediated) by pulmonary function (8,20). In a final model ( Table 2, Model H), we added terms for a number of potential confounders that might affect these associations with mobility disability.…”
Section: Resultsmentioning
confidence: 79%
“…Raw scores from each of the three averaged component pulmonary measures were converted to z scores using the means and standard deviations computed from the entire cohort. A composite pulmonary function score was created by converting the raw score from FVC, FEV 1 , and PEF to z scores using the mean and standard deviation from all participants at baseline (Table 1) and averaging z scores for these three measures together as previously described (8).…”
Section: Assessment Of Pulmonary Functionmentioning
confidence: 99%
See 1 more Smart Citation